PENGARUH KEPEMIPINAN, MOTIVASI DAN KEDISPLINAN TERHADAP KOMITMEN ORGANISASI DAN DAMPAKNYA TERHADAP KINERJA PEGAWAI PADA DINAS PERTANIAN KABUPATEN PIDIE - Cut Italina; Apridar Apridar; Ratna Ratna (J-MIND (Jurnal Manajemen Indonesia), 2020)
This study tested the influence of workload, quality of work life and work motivation against the performance of the employees, as well as testing the effect of mediation from the variable job satisfaction. The sample in this research are 114 employees remain Civil Records residence and Office of Lhokseumawe, North Aceh Regency. Analysis tool used is the analysis of the path (path analysis) with the SEM methods (structural equation modelling) using Amos. The results showed that each variable workloads, quality of working life is a positive and significant effect against the working motivation and work performance and motivation variables mediate the work load with variable performance partially mediation and work motivation variables mediate the quality of working life with full performance variables of mediation. Keywords: workload, quality of working life, Employment, Motivation and performance of Employees